Sexual Assault and Trauma as Reflected in Amadu Maddy’s “No Past No Present No Future” and Zakes Mda’s “The Madonna of Excelsior” - Abera Kassaw; Melakneh Mengistu (Richtmann Publishing, 2023)
Violence such as rape has been and continues to be the major problem in Africa. It is because defective family dynamic, sexualized racism, rape myths, patriarchal dominance, low legal system response to victims’ cases etc. often exert ever more significant obstacles in bringing a paradigm shift in people’s understanding towards victim reaction to sexual assault. Thus, it is vital to create a more trauma informed society and legal system in order to reduce the rate of sexual assault and to develop more effective criminal justice system responses to sexual assault cases. To this end, literary texts can play a paramount role since it can be used as a signpost to display victims’ reaction to sexual assault. Therefore, the main objective of this article was to undertake a critical examination of the traumatic impacts of sexual assault reflected in Amadu’s Novel “No Past No Present No Future” and Mda’s novel “The Madonna of Excelsior”, hoping to send signals to researchers to see the immense contribution which literary works can have to bring a paradigm shift in people’s understanding towards the drastic emotional, and psychological damages of rape. A trauma theory dominantly informed by Freud, and Van der Kolk and Greenberg was applied to analyze and discuss the causes of sexual assault and its resultant impact towards the victim characters in the novels under study. The study findings revealed that betrayal and negative heterosexual encounters as the causes of trauma and eventual PTSD in Amadu’s novel: “No Past No Present No Future”. In addition, the study has also found that homosexuality has been presented as the haven for the traumatized character to come at peace with his present condition leaving his traumatic experience behind. On the other hand, sexualized racism, racial injustice, and poverty caused sexual victimization of the major character in the Mda’s novel “The Madonna of Excelsior”. In addition, the study also found that rape exposed the victim character to experience trauma, which was very hard to bear, and its impact cut through the victim character’s life with emotional and psychological scars left behind. Furthermore, the study revealed that the victim character became prone to having flashback to memories which is a strong sign that PTSD develops in the novel “The Madonna of Excelsior”. Based on these findings, using literary texts which specifically focus on the consequences of sexual assault to educate society about victims’ reaction to rape is inexorably advisable and researchers in psychology can hopefully use the implications in this study to explore further the role of literature in reducing violence including rape and creating a health community life. Received: 8 January 2023 / Accepted: 19 February 2023 / Published: 6 March 2023